Penerapan Perhitungan Harga Pokok Produksi Menggunakan Metode Job Order Costing untuk Menentukan Harga Jual pada UD. Jati Makmur di Jombang - Andrean Salasa; Sri Rahayuningsih (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
The results of the data analysis show that the Cost of Production for the order of 31 units of school desks according to UD's calculations. Jati Makmur is Rp. 4,433,000, while according to the calculation of the job order costing method of Rp. 5,557,234, the Cost of Production for the order of 31 units of school chairs is Rp. 3,002,000, while according to the calculation of the job order costing method is Rp. 4,226,234. The Cost of Production calculated using the job order costing method is higher than according to UD's calculations. Jati Makmur, this is because the job order costing method is more accurate, all costs are clearly detailed, be it direct raw material costs, direct labor costs, and overhead costs, so that there is a difference in the Cost of Production caused by UD. Jati Makmur did not detail and group the components of production costs, namely the cost of raw materials, direct labor costs, and overhead costs. An inaccurate calculation of the Cost of Production will affect the determination of profits to not be in accordance with the company's wishes.